Targeted Inactivation of the Mouse Locus Encoding Coagulation Factor XIII-A: Hemostatic Abnormalities in Mutant Mice and Characterization of the Coagulation Deficit - Lauer, Peter; Metzner, Hubert J.; Zettlmeißl, Gerd; Li, Meng; Smith, Austin G.; Lathe, Richard; Dickneite, Gerhard (Thrombosis and Haemostasis, 2002)
Blood coagulation factor XIII (FXIII) promotes cross-linking of fibrin during blood coagulation; impaired clot stabilization in human genetic deficiency is associated with marked pathologies of major clinical impact, including bleeding symptoms and deficient wound healing. To investigate the role of FXIII we employed homologous recombination to generate a targeted deletion of the inferred exon 7 of the FXIII-A gene. FXIII transglutaminase activity in plasma was reduced to about 50% in mice heterozygous for the mutant allele, and was abolished in homozygous null mice. Plasma fibrin γ-dimerization was also indetectable in the homozygous deficient animals, confirming the absence of activatable FXIII. Homozygous mutant mice were fertile, although reproduction was impaired. Bleeding episodes, hematothorax, hematoperitoneum and subcutaneous hemorrhage in mutant mice were associated with reduced survival. Arrest of tail-tip bleeding in FXIII-A deficient mice was markedly and significantly delayed; replacement of mutant mice with human plasma FXIII (Fibrogammin® P) restored bleeding time to within the normal range. Thrombelastography (TEG) experiments demonstrated impaired clot stabilization in FXIII-A mutant mice, replacement with human FXIII led to dose-dependent TEG normalization. The mutant mice thus reiterate some key features of the human genetic disorder: they will be valuable in assessing the role of FXIII in other associated pathologies and the development of new therapies.
Keywords: Inactivation of FXIII gene; bleeding disorder; thrombelastography; factor XIII substitution; fibrin γ-dimerisation